The Endogenous Plasma Small RNAome of Rheumatoid Arthritis. Issue 2 (8th January 2020) - Ormseth, Michelle J.; Solus, Joseph F.; Sheng, Quanhu; Ye, Fei; Song, Haocan; Wu, Qiong; Guo, Yan; Oeser, Annette M.; Allen, Ryan M.; Vickers, Kasey C.; Stein, C. Michael
Abstract : Objective: Small RNA (sRNA) sequencing has revealed new sRNA classes beyond microRNAs (miRNAs). These sRNAs can regulate genes and act as biomarkers. The aim of this study was to determine if the endogenous plasma sRNA landscape is altered in patients with rheumatoid arthritis (RA) compared with control subjects and to determine its association with disease‐related parameters in RA. Methods: sRNA sequencing was performed on plasma from 165 RA and 90 control subjects who were frequency‐matched for age, race, and sex. Endogenous sRNAs, such as miRNAs, isomiRs, sRNAs derived from small nuclear RNAs (snDRs), small nucleolar RNAs (snoDRs), Y RNAs (yDRs), transfer‐derived RNAs (tDRs), long noncoding RNAs (lncDRs) as well as miscellaneous sRNAs (miscRNAs), were quantified using Tools for Integrative Genome analysis of Extracellular sRNAs (TIGER). Individual and categories of sRNAs were compared between RA and controls, and significantly altered sRNAs and sRNA categories were correlated with disease activity and general laboratory measures in RA. Results: Patients with RA had more miRNAs (1.42‐fold, P = 0.01), more tDRs (1.14‐fold, P = 0.04), and fewer yDRs (−1.41‐fold, P = 0.009) compared with control subjects. Disease duration was inversely associated with yDRs. Disease‐related parameters, such as Disease Activity Score‐28 (DAS28), swollen joint count, and inflammatory markers were significantly positively associated with tDRs and miscRNAs, and miR‐22‐3p and related sequences and isomiRs were most significantly associated with DAS28. Conclusion: Endogenous plasma sRNAs are altered in RA compared with control subjects. Although individual miRNAs have been well studied and many are excellent biomarkers in RA, several non‐miRNA sRNAs were significantly associated with disease‐related parameters as classes and may represent novel biomarkers for RA.